1988
DOI: 10.1161/01.cir.77.6.1319
|View full text |Cite
|
Sign up to set email alerts
|

Does desmopressin acetate reduce blood loss after surgery in patients on cardiopulmonary bypass?

Abstract: It has been suggested that desmopressin acetate (DDAVP) Since a significant platelet function defect may be the primary cause of hemorrhage, the use of platelet concentrateN and prostacyclin has been suggested.2', 17, A defect in ristocetin-induced platelet aggregation has been described in these patients,2 suggesting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(37 citation statements)
references
References 17 publications
0
34
0
1
Order By: Relevance
“…Nine studies were excluded because no clinical outcome other than blood loss was available, [7][8][9][10][11][12][13][14][15] eight studies were found not to be randomized after more thorough analysis, [16][17][18][19][20][21][22][23] five studies concerned cardiac surgery in child- ren, [24][25][26][27][28] and there was one double report. 29,36 66,75,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In addition, 12 studies compared treatment with the conventional dose of aprotinin with lower doses of aprotinin. 30,38,40,41,44,46,48,50,56,…”
Section: Literature Search and Methodological Gradingmentioning
confidence: 99%
“…Nine studies were excluded because no clinical outcome other than blood loss was available, [7][8][9][10][11][12][13][14][15] eight studies were found not to be randomized after more thorough analysis, [16][17][18][19][20][21][22][23] five studies concerned cardiac surgery in child- ren, [24][25][26][27][28] and there was one double report. 29,36 66,75,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In addition, 12 studies compared treatment with the conventional dose of aprotinin with lower doses of aprotinin. 30,38,40,41,44,46,48,50,56,…”
Section: Literature Search and Methodological Gradingmentioning
confidence: 99%
“…26 In a randomized trial comparing DDAVP versus placebo, we could not confirm that DDAVP reduces the total blood loss and transfusion requirements, although it was observed to significantly reduce intraoperative blood loss. 16 These results were later confirmed by Hackmann et al 27 Furthermore, four additional studies did not find significant improvement in postoperative blood loss,28-31 and one report shows that the total postoperative blood loss and the red cell transfusion rates were significantly higher in the DDAVP group than in the control group, which could be related to the DDAVP-induced TPA release from endothelial cells and subsequent fibrinolysis. 32 Since, as suggested by our findings, the administration of DDAVP was effective only in reducing intraoperative bleeding, we decided to administer a second dose 6 hours after surgery to establish whether it could also improve the postoperative blood loss.…”
Section: Discussionmentioning
confidence: 83%
“…Até meados da década de 1980, as estratégias farmacológicas mais empregadas para reduzir o sangramento cirúrgico consistiam na utilização de desmopressina e prostaciclinas, com resultados pouco efetivos [27][28][29] . Os antifibrinolíticos inibem a fibrinólise e, conseqüentemen-te, impedem ou diminuem a formação dos PDF, que têm ação deletéria sobre a função plaquetária.…”
Section: Antifibrinolíticosunclassified
“…Until the middle of the decade of 1980, pharmacological strategies used more often to reduce surgical bleeding consisted of desmopressin and prostacyclins, which were not very effective [27][28][29] . Antifibrinolytics inhibit fibrinolysis and, consequently, prevent or reduce the formation of FDP, which have deleterious effects on platelet function.…”
Section: Antifibrinolyticsmentioning
confidence: 99%